Optimizing inhalation therapy in the aspect of peak inhalation flow rate in patients with chronic obstructive pulmonary disease or asthma - Jian-lan Hua; Xiao-fen Ye; Chun-ling Du; Ning Xie; Jie-qing Zhang; Man Li; Jing Zhang (BMC Pulmonary Medicine, 2021)
Abstract Background Pressurized metered dose inhalers (pMDIs) and dry powder inhalers (DPIs) are commonly used drug-delivering devices for patients with chronic airway diseases. Appropriate peak inhalation flow rate (PIFR) and inhaler technique is essential for effective therapy. We aimed at optimizing inhalation therapy through the analysis of PIFRs in patients with chronic obstructive pulmonary disease (COPD) or asthma as well as the effect of technique training using In-Check DIAL® to help patients to achieve their optimal inspiratory flow rates. Methods The study continuously enrolled patients who were diagnosed as COPD or asthma from respiratory clinics. PIFRs were described and analyzed between the newly-diagnosed and follow-up patients, and the stable and acute exacerbation patients, respectively. Every participant was trained inhaler technique using In-Check DIAL®. PIFRs before and after training was compared by self-control analysis. Results Among a total of 209 patients, the average age was 56.9 years. For DPIs users, 10.8% patients had a PIFR < 30 L/min and 44.1% patients had a PIFR ≥ 60 L/min before technique training. After technique training, scarcely patient (1.5%) had a PIFR < 30 L/min, and 60.5% patients had a PIFR ≥ 60 L/min. The patient’s average PIFR increased by 5.6L/min after training. The increase in PIFR before and after training was significant (p < 0.001) for most patients, but no significant variation was found in patients with acute exacerbation (p = 0.822). Conclusions A considerable number of patients with COPD or asthma were not able to achieve the minimum or optimal PIFR for DPIs. Inhaler training can increase patients’ PIFRs and improve their ability to use DPIs. Trail registration The study has registered in chictr.org.cn (ChiCTR1900024707) and been approved by the Ethics Committee of Zhongshan Hospital of Fudan University (B2019-142).